2023
DOI: 10.3390/nu15122801
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Health Status of Spanish Schoolchildren Based on Nutrimetry, Lifestyle and Intestinal Parasites

Abstract: Malnutrition in Spanish schoolchildren, and its relationship with lifestyles, has been studied, but Nutrimetry (a nutritional status indicator), and data on intestinal parasitism and its risk factors, have never before been taken into account. A total of 206 children aged 3–11 years, from two schools in the Valencian Community, participated. Demographic characteristics, diet, lifestyles, behavioural habits and anthropometric (weight, height) and coproparasitological data were collected. Nutrimetry was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In a study conducted on a group of 206 schoolchildren in Spain, it was found that the incidence of intestinal parasitosis is as high as 49.5%, while the incidence of multiple infections was estimated at 14.6%. Infections were mainly caused by Giardia intestinalis, Blastocystis sp., and Enterobius vermicularis [14]. It is worth noting that Spain is a country with a socioeconomic status similar to Poland.…”
Section: Epidemiology Of Intestinal Parasitic Infectionsmentioning
confidence: 99%
“…In a study conducted on a group of 206 schoolchildren in Spain, it was found that the incidence of intestinal parasitosis is as high as 49.5%, while the incidence of multiple infections was estimated at 14.6%. Infections were mainly caused by Giardia intestinalis, Blastocystis sp., and Enterobius vermicularis [14]. It is worth noting that Spain is a country with a socioeconomic status similar to Poland.…”
Section: Epidemiology Of Intestinal Parasitic Infectionsmentioning
confidence: 99%